Measurement Invariance Across Gender and Major: The Love of Money Among University Students in People’s Republic of China - Du, Linzhi (Journal of business ethics, 2005)
This study investigates measurement invariance of the 17-item-4-factor Love of Money Scale (LOMS) (Rich, Motivator, Success, and Important) across gender and college major among university students in People’s Republic of China. Results revealed configural (factor structures) invariance across gender. Metric (factor loadings) invariance across gender was not achieved based on chi-square change, but achieved based on fit indices change between unconstrained and constrained multi-group confirmatory factor analysis (MGCFA). Both configural invariance and metric invariance (chi-square change and fit indices change) were achieved across college major (law, sociology, and political science). Results of this study suggest that the Love of Money Scale, developed in the U.S., has achieved measurement invariance in this student sample in China. Future researchers will have some confidence in using this measurement when they examine the love of money in Chinese management and organizational studies.